Toward an Integrated ASEAN Labor Market Prospects and Challenges for CLMV(1) Countries - Hoàng, Nguyễn Huy (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2013)
Abstract: Recently, at the 22 nd ASEAN Labor Ministers Meeting (ALMM) held in Cambodia in May 2012 with the theme “Enhancing social protection and skill development”, Prime Minister Hun Sen continued emphasizing the role of the integrated labor market among ASEAN member countries for building the ASEAN Community (AC) as well as the ASEAN Economic Community (AEC) in 2015. The accomplishment of AEC would be considered as an important content to promote building an ASEAN labor market freer, more efficient and improving the competitiveness of member countries, especially for the less developed countries such as CLMV. However, an Integrated ASEAN Labor Market (IALM) would also pose some challenges for CLMV countries. In this context, this paper aims to focus on resolving the following two main questions: (1) What is the content of the ASEAN commitments for promoting an Integrated ASEAN Labor Market and the IALM would be a more complete market for free movement of skilled and professional labor within ASEAN countries?; (2) What are the prospects and challenges for CLMV countries? It is important to note here that in this paper, we focus only on a theoretical (not empirical) analysis of the integrated labor market in ASEAN and prospects as well as challenges for CLMV countries. Thus, the paper just provides theoretically analytical information and outcomes of the proposed research. Keywords: ASEAN Economic Community, Integrated ASEAN Labour Market, CLMV countries.